Language reorganization in aphasics: An electrical stimulation mapping investigation - Lucas, Timothy H. (2008)
OBJECTIVE: The purpose of this investigation was to determine whether clinical speech deficits following brain injury were associated with functional speech reorganization. METHODS: Across an 18 year interval, 11 patients with mild to moderate speech deficits underwent language mapping as part of their treatment for intractable epilepsy. These ‘aphasics’ were compared to 14 matched ‘controls’ with normal speech also undergoing epilepsy surgery. Neuroanatomical data were compared to quantitative language profiles and clinical variables. RESULTS: Cortical lesions were evident near speech areas in all aphasia cases. As expected, aphasics and controls were distinguished by quantitative language profiles. The groups were further distinguished by the anatomical distribution of their speech sites. A significantly higher proportion of frontal speech sites was found in patients with prior brain injury, consistent with frontal site recruitment. The degree of frontal recruitment varied as a function of patient age at the time of initial brain injury—earlier injuries were associated with greater recruitment. The overall number of speech sites remained the same following injury. Significant associations were found between the number of the speech sites, naming fluency and the lesion proximity in the temporal lobe. CONCLUSIONS: Language maps in aphasics demonstrated evidence for age-dependent functional recruitment in the frontal, but not temporal, lobe. The proximity of cortical lesions to temporal speech sites predicted the overall extent of temporal lobe speech representation and performance on naming fluency. These findings have implications for neurosurgical planning in patients with preoperative speech deficits.